The great realignment: Navigating catastrophe and capital in the decade ahead - Sitas, Ari (New Agenda: SA Journal of Social and Economic Policy, 2026)
The defining crises of our era will require a great realignment of global forces, middle countries, the coalition of progressive movements – marginalised communities, women’s groups, workers, the unemployed and the working poor – to shape a new reality going forward. ARI SITAS examines the unfolding process currently creating disastrous instability and friction, and argues for the need for creative efforts to transform the catastrophic reality into an inclusive developmental world order.